1994
DOI: 10.1038/bjc.1994.168
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance circumvention by a new triazinoaminopiperidine derivative S9788 in vitro: definition of the optimal schedule and comparison with verapamil

Abstract: Summary The current work was undertaken to investigate the importance of exposure sequence and duration in achieving the maximum reversal action of S9788 on doxorubicin (DOX) cytotoxicity against cells that exhibit the (MDR) multidrug resistance phenotype: the MCF7/DOX cell line. Accumulation and release of DOX were examined in this cell line. The reversal effect was compared with that obtained with verapamil. S9788 activity was schedule dependent: when comparing incubation with S9788 before or after treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Therefore, this study shows that, using this schedule, effective concentrations of S9788 can be reached at nontoxic doses in patients. The high total body clearance and short initial half-life of S9788 that we found support the rationale for prolonged infusion over bolus infusion of S9788, as was suggested by others (Perez et al, 1993;Julia et al, 1994;Soudon et al, 1995). Compared with treatment with doxorubicin alone, patients treated with doxorubicin plus S9788 experienced a significant increase in the occurrence of WHO grade 3-4 granulocytopenia, but not in the occurrence or severity of other toxicities.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, this study shows that, using this schedule, effective concentrations of S9788 can be reached at nontoxic doses in patients. The high total body clearance and short initial half-life of S9788 that we found support the rationale for prolonged infusion over bolus infusion of S9788, as was suggested by others (Perez et al, 1993;Julia et al, 1994;Soudon et al, 1995). Compared with treatment with doxorubicin alone, patients treated with doxorubicin plus S9788 experienced a significant increase in the occurrence of WHO grade 3-4 granulocytopenia, but not in the occurrence or severity of other toxicities.…”
Section: Discussionsupporting
confidence: 85%
“…Structurally, S9788 does not belong to any of the classes of compounds known to reverse MDR. It increases the intracellular accumulation and retention of doxorubicin, vincristine and vinblastine in resistant cell lines displaying the Pgp-mediated MDR phenotype Efferth et al, 1993;Hill et al, 1993;Huet et al, 1993;Julia et al, 1994;Merlin et al 1994). These studies also showed that modulation of resistance is obtained in both drug-selected and inherently resistant cell lines, and that S9788 is more potent than verapamil at equimolar concentrations.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…MCF7/DOX cells (Julia et al 1994) were obtained from Dr F Pinguet (CRLC, Montpellier, France). Monolayer cell cultures were grown in Ham's F-12/Dulbecco's modified Eagle's medium (1:1) (F12/DMEM) supplemented with 10% foetal calf serum (FCS) (Life Technologies, Cergy-Pontoise, France) and antibiotics.…”
Section: Plasmids Containing P21mentioning
confidence: 99%
“…This triazineaminopiperidine derivative has no structural similarities to other known MDRmodulating agents. In vitro, S9788 has been shown to effectively reverse MDR-dependent resistance to doxorubicin, vincristine and a variety of cytotoxic drugs [19,20]. At a concentration of 5 uM it was 2.5-317 times more potent than verapamil in reversing MDR [21][22][23].…”
Section: Introductionmentioning
confidence: 99%